Fungal flora of rizosphere of Phaseolus lunatus «pallar» from Ica, Peru - Arenas, Julissa (2005)
This work analysed the fungal flora from the rizosphere of Phaseolus lunatus «pallar» in the farm San Camilo, Ica, for determination of possible pathogenic fungi. Eighty rizosphere samples were taken of the of P. lunatus plants, someones healthy and others with disease symptoms. For the isolation of the fungi, was used the dilution plates technique. Colonies were assessed after of 3 to 5 days of incubation on laboratory temperature. Twelve species had been identified that belonging 6 genus: Alternaria, Aspergillus, Cladosporium, Fusarium, Penicillium y Rhizopus. Species dominants were Cladosporium sp with 120 x 103 UFC/g, Aspergillus niger with 88 x 103 UFC/g and Aspergillus terreus with 74 x 103 UFC/g.